ANALISIS EFISIENSI PRODUKSI DAN PERILAKU PETANI DALAM MENGHADAPI RISIKO PADA USAHATANI JAGUNG DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Ibrohim Saputra Saputra; Dyah Aring Hepiana Lestari; Adia Nugraha (Lampung University, 2018)
The study aims to analyze the factors that affect production of corn farming, the production efficiency of corn farming, and the behaviour of farmers in facing risks of corn farming. Data were collected in Natar District South Lampung Regency in January – February 2017. The total of respondents were 58 farmers nonmembers of farmer groups who were chosen by using simple random sampling. The primary data were obtained from direct interviews with the corn farmers and secondary data were obtained from several related institutions. Data were analyzed using Cobb-Douglas production function, economic efficiency analysis by calculating the NPMxi/Pxi value, and quadratic utility function. The results of this research showed the factors that affected the production of corn farming were land area, seed, urea fertilizer, and SP-36 fertilizer. The corn farming was not economically efficient yet. Most of farmers were neutral in facing risks, only 1.72 percent farmers were risk averters, and no risk taker farmers. Key words: behaviour, corn, efficiency, farmers, risks